Association between Maternal Depression and Sleep Disorders in Toddlers: A Case Report - Francisca Bastos Maia; Vânia Martins Miranda (Revista Portuguesa de Psiquiatria e Saúde Mental, 2023)
Poor sleep quality in childhood can lead to socio-emotional and academic problems. In early childhood, sleep is mostly influenced by environmental factors, such as the mother’s mental health. The aim of this case report is to expand the body of knowledge surrounding the association between sleep disturbances in toddlers and maternal depression. An 18-month-old child was referred to a Child Psychiatry consultation due to multiple nocturnal awakening almost every night since he was 3 months old. The mother reports depressive symptoms. It was concluded that the child met criteria for night awakening disorder. The treatment plan included sessions to promote parenting skills and the use of prolonged-release melatonin. The literature shows that maternal depressive symptoms are related to difficulties in initiating and maintaining sleep in young children, and it is important to diagnose and treat this symptomatology to mitigate its impact on these children’s sleep.